Pharmacokinetics of pentoxifylline and its 5-hydroxyhexyl metabolite following intravenous administration in cattle - Uney, Kamil; Tras, Bunyamin; Corum, Orhan; Yildiz, Ramazan; Maden, Mehmet (Springer Science and Business Media LLC, 2018)
This study investigated the pharmacokinetics of pentoxifylline (PTX) and its 5-hydroxyhexyl metabolite (M-I) after single-dose intravenous (IV) administration (10 mg/kg) of PTX in six healthy cattle. The safety of PTX was evaluated by clinical observation and biochemical analysis. Plasma concentrations of PTX and M-I were simultaneously determined by reverse-phase high performance liquid chromatography. Pharmacokinetic parameters were calculated using non-compartmental methods. Salivation and discomfort were observed for 2 h following the drug administration. Serum direct bilirubin, total bilirubin, and phosphorus levels at 24 h following the drug administration were significantly different from the control values (0 h) (P < 0.05). Pharmacokinetic variables of PTX were characterized by a short terminal elimination half-life (1.05 ± 0.19 h), a large volume of distribution (6.30 ± 1.76 L/kg), and high total body clearance (5.31 ± 1.27 L/h/kg). The mean ratio between the area under the concentration-time curves of M-I and PTX was 1.34. These results indicate that single-dose administration of PTX at 10 mg/kg IV in cattle resulted in therapeutic concentrations similar to those observed in humans and horse. However, further studies are necessary to determine the safety and pharmacokinetics following repeated administrations of PTX.
Keywords: M-I metabolite; Phosphodiesterase Inhibitors; Area Under Curve; Injections, Intravenous; Animals; Pharmacokinetics; Administration, Intravenous; Cattle; Pentoxifylline; Intravenous; Chromatography, High Pressure Liquid; Half-Life; 2. Zero hunger; 3. Good health